EARLY DETECTION AND COUNSELLING OF ANXIETY DISORDERS IN CHILDREN WITH SYSTEMIC LUPUS ERYTHEMATOSUS - Wulandari, Desy; Barlianto, Wisnu; Nugroho, Susanto (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2025)
Introduction: Paediatric Systemic Lupus Erythematosus (pSLE) is a chronic autoimmune disease that affects the quality of life of patients. Anxiety is a mental health problem that is rarely addressed in Indonesia. There are still many instances of children and adolescents with anxiety due to the duration of therapy, the severity of the disease, psychological conditions, and support from the environment and family. Therefore, the detection of anxiety disorders in children and adolescents really needs to be improved. This community service activity aims to provide counselling on anxiety detection in children with SLE. Methods: This community service has been carried out in June 2024 at Polyclinic of Dr Saiful Anwar Hospital Malang. The counselling about SLE, mental health, and the relationship between the two was done directly to the paediatric and adolescent patients with SLE and the evaluation was done through questionnaires using the Screen for Child Anxiety and Related Emotional Disorders (SCARED). Results: After the delivery of content related to SLE and mental health as well as the completion of questionnaires, from this activity there were 12.5% of children and adolescents from 32 patients with systemic lupus erythematosus disease who experienced anxiety disorders so that further evaluation and intervention were needed. Conclusion: Although the number of patients who did not experience anxiety was more than patients who experienced anxiety in this community service activity, psychological support to maintain optimal mental health is needed besides primary treatment for paediatric and adolescent patients with chronic illnesses.